Pengaruh Model Pembelajaran Connecting, Organizing, Reflecting, Extending (CORE) terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Arinta Rara Kirana (Lentera: Jurnal Ilmiah Kependidikan, 2025)
The problems studied in this study are related to the less than optimal achievement of students' mathematical problem-solving abilities. The purpose of this study was to determine the effect of the CORE learning model on the mathematical problem-solving abilities of grade VIII students in the Odd Semester of SMP Negeri 34 Bandar Lampung in the 2025/2026 Academic Year. This study used an experimental method with the population in this study being all grade VIII students of SMP Negeri 34 Bandar Lampung consisting of 7 classes. While the sample was taken from two classes, namely class VIII C as the experimental class that applies the CORE learning model, and class VIII A as the control class that applies the conventional learning model. The sample was taken using the Cluster Random Sampling technique. To determine students' mathematical problem-solving abilities, the author conducted a test in the form of five essay questions that had previously been tested for validity and reliability. Hypothesis testing in this study used the t-hit formula and obtained a value of t = 3,51. From the t-distribution table at a significance level of 5%, it is known that t = 1,67, so , which means that the average mathematical problem-solving ability of students using the CORE learning model is higher than the average mathematical problem-solving ability of students using the conventional learning model.